PROFILE STUDY OF CASES OF DEATH DUE TO DROWNING (Journal of Forensic Medicine & Toxicology, 2015)
The aim of this study was to find out the pattern of cases of Drowning, to focus on impact of various factors and to evaluate the present situation about death due to drowning at Bhavnagar, Gujarat, India. A study was carried out on 70 cases of drowning, brought for postmortem examination at Sir T General Hospital and Government Medical College Bhavnagar, during the period of June 2010 to May 2012. This study throw some lights on the emerging trends that incidence of death due to drowning is increases in monsoon season, in male, lower socio economic status, poor education level. Most of the victims were from the age group of 21 to 30 years. In present study common place of Drowning was well followed by sea. We found that majority of cases died within 12 hours before starting of post mortem examination.
Keywords: Drowning; Impact factor; Bhavnagar